Adoption of electronic invoicing in Finnish SMEs: two complementary perspectives. (15th June 2006) - Edelmann, Jan; Sintonen, Sanna
Electronic invoicing is one of the latest innovations in the field of electronic business solutions, and the Finnish Information Technology (IT) industry has expected all the Finnish SMEs to adopt it widely. However, the adoption of electronic invoicing seems to be in the slow lane. This study was carried out to find out the reasons for the slow adoption rate of electronic invoicing by SMEs and stop the conjecturing about the reasons. The behaviour of current and potential users was studied in a survey conducted in South Karelia in the spring of 2005. The main advantage that e-invoicing offers is its potential in decreasing the clerical work and costs of the invoicing process, but it is also seen as a source of new business opportunity. To find out the reasons for the slow adoption rate, the survey results were first analysed statistically, and then the analysis was extended by the Strategic Options Approach (SOA) for a closer view.